2012
DOI: 10.1212/wnl.0b013e31826aac73
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of HLA-B*1502 genotyping in adult patients with newly diagnosed epilepsy in Singapore

Abstract: Because of the different population allele frequencies of HLA-B*1502 among different ethnic groups, genotyping for HLA-B*1502 and providing alternate AEDs to those who test positive is cost-effective for Singaporean Chinese and Malays, but not for Singaporean Indians. Population frequency of HLA-B*1502, PPV, duration of treatment relative to life expectancy, and costs of alternative drugs are the key drivers influencing cost-effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 21 publications
2
104
0
1
Order By: Relevance
“…Knowledge of the individual genetic profiles of the patients means costlier alternatives can be assigned to only those who cannot tolerate the cheaper medications, and this can produce significant cost savings to the health-care system even after including the price of pretreatment genetic screening. This was exactly the case for HLA-B*15:02 screening before carbamazepine prescription in East Asians, [33][34][35] delivering overall savings to the health-care system despite having to screen a greater number of patients to deliver the benefit to one patient. However, it should be reminded that the findings of cost savings are context-specific and not directly transferable across different health systems, such as the discovery of HLA-B*57:01 testing being not cost-effective for East and Southeast Asian populations, 36,37 despite being ascertained to be so in European populations.…”
Section: Swot Analysis Of Pharmacogenetics In Health Carementioning
confidence: 90%
See 1 more Smart Citation
“…Knowledge of the individual genetic profiles of the patients means costlier alternatives can be assigned to only those who cannot tolerate the cheaper medications, and this can produce significant cost savings to the health-care system even after including the price of pretreatment genetic screening. This was exactly the case for HLA-B*15:02 screening before carbamazepine prescription in East Asians, [33][34][35] delivering overall savings to the health-care system despite having to screen a greater number of patients to deliver the benefit to one patient. However, it should be reminded that the findings of cost savings are context-specific and not directly transferable across different health systems, such as the discovery of HLA-B*57:01 testing being not cost-effective for East and Southeast Asian populations, 36,37 despite being ascertained to be so in European populations.…”
Section: Swot Analysis Of Pharmacogenetics In Health Carementioning
confidence: 90%
“…The promising scenario where being genotype-negative confers almost zero risk of adverse drug reactions (or equivalently, a specificity of almost 100% for genetic testing) really only extends to HLA-B*15:02 and HLA-B*57:01 for carbamazepine 33 and abacavir, 8 respectively, whereas most of the genetic markers hardly achieve such dichotomy for clinical decisions. For example, the loss-of-function alleles in CYP2C19 accounts for only 12% of clopidogrel response variability in spite of the fact that the heritable variability is estimated to be 72%, 42,43 and this means there are other genes involved on top of CYP2C19 or other yet unknown markers in CYP2C19 that contribute to explain the variation in clopidogrel response.…”
Section: Imperfect Understanding Of Genetic Determinants Of Drug Respmentioning
confidence: 99%
“…28 Penelitian uji efektifitas di Thailand menunjukkan hasil efektif dan dapat diterapkan pada populasi lain apabila dijumpai frekuensi HLA-B*15:02 yang tinggi. 29 Melalui analisa filogenetik diketahui bahwa nenek moyang populasi merupakan hasil sebaran migrasi manusia dari daratan Asia dan India sehingga mempunyai kedekatan hubungan kekerabatan dengan populasi di daratan Asia dan India. Berikutnya disebutkan pada populasi di Indonesia ditemukan frekuensi alel HLA-B*15:02 yang tinggi (11,6%).…”
Section: Prevalensi Ssj-net Disebabkan Karbamazepinunclassified
“…The study in Malaysia recommended to adopt the in-house HLA-B * 1502 screening system, which is much more cost-effective than using commercial kits, to facilitate routine genotyping in the clinical setting [43]. The study in Singapore demonstrated the cost-effectiveness of HLA-B * 1502 testing [44]. Therefore, the Ministry of Health in Singapore recommends HLA-B * 1502 genotyping before CBZ therapy in CBZ-naïve patients who have Asian ancestry, and patients from the Ministry of Health-funded restructured hospitals and institutions will get a subsidy rate of 75% of the test cost (http://www.hsa.gov.sg/content/hsa/en/Health_Products_Regulation/Safety_Information_and_Product_Recalls/Product_Safety_Alerts/2013/recommendations_for.html).…”
Section: Clinical Pharmacogenomics Of Drug-induced Sjs/ten: Associatimentioning
confidence: 99%
“…SE Asia is the hotbed of SJS/TEN triggered by CBZ. Since the prospective clinical trial, Taiwan succeeded in the complete prevention of SJS/TEN by establishing the HLA-B * 1502 pharmacogenomics test, and this strategy provides better value for money than the avoidance of CBZ enforced in several healthcare systems, including Hong Kong, Singapore and Thailand [42,44]. Given the high prevalence of HLA-B * 1502 in SE Asia, implementing pharmacogenomics testing would dramatically reduce the SJS/TEN incidence triggered by CBZ in this region.…”
Section: Regional Potential For the Prevention Of Drug-induced Sjs/tementioning
confidence: 99%